Regulatory framework on platform workers’ right to safe and healthy working conditions in malaysia; a business and human rights approach - Makhtar, Maheran; Abd Ghadas, Zuhairah Ariff; Mat Yaman, Khariyah (The Japan Association of Occupational Health Law, 2024)
The issue of platform workers’ right to safe and healthy working conditions in Malaysia is an important one that cannot be overlooked from both a business and human rights perspective. As such, this paper aims to investigate the available options for regulators and policymakers to improve and expand the regulatory framework governing gig work, focusing on addressing the unique challenges platform workers face. Furthermore, this paper also delves into the impact of regulatory failure on atypical workers, emphasizing the gaps in coverage as well as enforcement inefficiencies that significantly impact workers’ safety and health while on the job. This paper highlights the importance of establishing comprehensive regulations protecting platform workers’ rights to safe and healthy working conditions. It also emphasizes that such regulations must be implemented effectively to safeguard against any potential violations or failures that could negatively impact workers’ well-being while performing their duties. Ultimately, stakeholders across various industries need to collaborate closely with regulators and policymakers to develop solutions that address these pressing concerns within Malaysia’s growing gig economy sector.